A phase-transited lysozyme coating doped with strontium on titanium surface for bone repairing via enhanced osteogenesis and immunomodulatory - Zhang, Yu; Chen, Yu; Shi, Yidan; Hu, Hongkun; Dai, Zhongyu; Liu, Zhichen; Li, Xuanan (Frontiers in Cell and Developmental Biology, 2025)
IntroductionTitanium is currently recognized as an excellent orthopedic implant material, but it often leads to poor osseointegration of the implant, and is prone to aseptic loosening leading to implant failure. Therefore, biofunctionalization of titanium surfaces is needed to enhance their osseointegration and immunomodulation properties to reduce the risk of implant loosening. We concluded that the utilization of PTL-Sr is a direct and effective method for the fabrication of multifunctional implants.MethodsIn this Study, phase-transited lysozyme (PTL) is deposited onto the surface of titanium (Ti) to construct a functional coating and strontium chloride solution was utilized to produce PTL coatings with Sr2+. The characterization of the strontium-doped PTL coatings (PTL-Sr) was tested by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX) and inductively coupled plasma atomic emission spectroscopy (ICP-AES). A series of cell and animal experiments were conducted to investigate the biological functions of PTL-Sr coatings.ResultsThe characterization indicates the successful preparation of PTL-Sr coatings. In vitro cellular experiments have demonstrated that it promotes M2 macrophage polarization and reduces inflammatory mediator production while promoting osteogenic differentiation of bone merrow mesenchymal stem cells (BMSCs). The in vivo subcutaneous implantation model demonstrated its good immunomodulatory and angiogenic properties.DiscussionTitanium with PTL-Sr coatings promote biomineralization and immunomodulation, which is suitable for orthopedic applications. Further mechanistic exploration and studies using animal models is necessary to enhance the understanding of the clinical applicability of modified titanium.